(Photo-)electrochemical reactions on semiconductor surfaces, part B: III-V surfaces–atomic and electronic structure - Hajduk, Andreas; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Guidat, Margot; Löw, Mario; Ullmann, Fabian; Moritz, Dominik C.; Hofmann, Jan P.; Krischok, Stefan; Runge, Erich; Schmidt, Wolf Gero; Jaegermann, Wolfram; et al. (Encyclopedia of Solid-Liquid Interfaces)

Verben in Szenen. Grammatikgespräche im Sprachvergleich - Topalović, Elvira; Blachut, Alisa (Grundschule Deutsch)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

Who Deserves Credit? Banks for the Virtuous in Rural China - von Blomberg, Marianne; Reijers, Wessel (Journal of Contemporary China)

City 5.0: Citizen involvement in the design of future cities - Becker, Jörg; Chasin, Friedrich; Rosemann, Michael; Beverungen, Daniel; Priefer, Jennifer; Brocke, Jan vom; Matzner, Martin; del Rio Ortega, Adela; Resinas, Manuel; Santoro, Flavia; Song, Minseok; Park, Kangah; et al. (Electronic Markets)
Abstract A citizen-centric view is key to channeling technological affordances into the development of future cities in which improvements are made with the quality of citizens’ life in mind. This paper proposes City 5.0 as a new citizen-centric design paradigm for future cities, in which cities can be seen as markets connecting service providers with citizens as consumers. City 5.0 is dedicated to eliminating restrictions that citizens face when utilizing city services. Our design paradigm focuses on smart consumption and extends the technology-centric concept of smart city with a stronger view on citizens’ roadblocks to service usage. Through a series of design workshops, we conceptualized the City 5.0 paradigm and formalized it in a semi-formal model. The applicability of the model is demonstrated using the case of a telemedical service offered by a Spanish public healthcare service provider. The usefulness of the model is validated by qualitative interviews with public organizations involved in the development of technology-based city solutions. Our contribution lies in the advancement of citizen-centric analysis and the development of city solutions for both academic and professional communities.

Explaining the Technical Artifact Quarto!: How Gestures are used in Everyday Explanations - Lohmer, Vivien; Terfloth, Lutz; Kern, Friederike (First International Multimodal Communication Symposium - Book of Abstract)
Keywords: gesture; dual nature; explanations; architecture; relevance

Conference Report: Politics, Populism, Culture: The Politics of Populist Culture (20.-22.09.2023) - Althoff, Sebastian (Portal für Politikwissenschaft)

An elementary approach to the inverse first-passage-time problem for soft-killed Brownian motion - Klump, Alexander; Kolb, Martin (Journal of Applied Probability)
Abstract We prove existence and uniqueness for the inverse-first-passage time problem for soft-killed Brownian motion using rather elementary methods relying on basic results from probability theory only. We completely avoid the relation to a suitable partial differential equation via a suitable Feynman–Kac representation, which was previously one of the main tools.

Advancing Digital Collaboration: Barriers to Enterprise Social Media Adoption and how to Overcome them - Strich, Franz; Giermindl, Lisa; Mayer, Anne-Sophie; Fiedler, Marina (Hawaii International Conference on System Sciences 2023 (HICSS-56))
Advancing digital collaboration and fostering effective communication among a widespread workforce continues to be a perpetual challenge for companies. Organizations are progressively turning to Enterprise Social Media (ESM) because they promise new avenues for collaborative working. However, most ESMs fail to reach a wider adoption by the workforce, owing to an underutilization by the employees. To enhance the understanding of the underutilization phenomenon, we use affordance actualization theory as our theoretical lens to critically study the challenges employees face in their attempt to actualize respective ESM affordances. By analyzing comments from 992 frequent, infrequent, and discontinued ESM users from a large multinational company, we uncover four major challenges. By enhancing our understanding of ESM affordances and by incorporating the full spectrum from problem identification to solution, we provide practical advice for digital leaders and meaningful theoretical implications for the IS community.

Sarah Ihden (2000): Relativsätze im Mittelniederdeutschen. Korpuslinguistische Untersuchungen zu Struktur und Gebrauch. - Wallmeier, Nadine (Linguistische Berichte)

How Algorithmic Technologies Affect Employees’ Social Relationships - Mayer, Anne-Sophie; Strich, Franz; Watson-Manheim, Mary Beth; Fiedler, Marina (Academy of Management Proceedings)
The introduction of advanced algorithmic technologies to augment or automate employees’ work tasks increasingly transform employees’ social relationships. Through a qualitative, in-depth case study in the banking industry, we identify two different forms of algorithmic technologies that employees use. In doing so, we reveal how decision-taking technology negatively affects the quantity of social interactions with customers and colleagues, and consequently the quality of social relationships. However, we also uncover how a second set of algorithmic technologies, which is used for consultation, reduces the quantity of interactions, but enhances the quality of the social relationships with colleagues and customers. Based on six different aspects of social relations, we highlight commonalities and differences between algorithmic technologies with regard to their impact on employees' social relationships and derive relevant theoretical and practical implications.

Building professional holding environments for crowd work job crafting through online communities - Strunk, Kim Simon; Strich, Franz (Information Systems Journal)
Abstract Work is increasingly being organised via online platforms outside guiding organisational structures. Instead of having colleagues at work, crowd workers connect in online communities. We investigate how crowd workers build professional holding environments in online communities to compensate for the lack of organisational structures and we consider how they craft their crowd work activities to enhance their work experience and reduce its long‐term precarity. Following a qualitative research design, this paper uses 675 forum interactions collected across six online communities. Based on our findings, we propose the concept of professional holding environments and provide a model for building such holding environments and job crafting in online communities. We thereby expand previous research on holding environments comprised of family members and friends by revealing the impact of professional online communities and their role in professionalisation and crafting supportive social structures in online crowd work.

Kryptowertpapiere - Bartlitz, David (iff Infobrief)

Brief Announcement: Distributed Construction of Near-Optimal Compact Routing Schemes for Planar Graphs - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (Proc. of the 42nd ACM Symposium on Principles of Distributed Computing (PODC '23))

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization of trehalose, in contrast to other saccharides, leads to the formation of microspheres with a bimodal size distribution. The microspheres develop hierarchical porosity with micro-, meso-, and macro-pores after pyrolysis.

Colloid Science—as modern as ever - Fery, Andreas; Gradzielski, Michael; Richtering, Walter; Schmidt, Claudia (Colloid and Polymer Science)

Colloid and Polymer Science, Special Issue: 100 Years Colloid Society / Colloid Science - as Modern as Ever (Colloid and Polymer Science)

The Dark Side of International Student Mobility: Which Students Suffer from Loneliness? - Bilecen, Basak; Diekmann, Isabell; Faist, Thomas
For students, study abroad has its advantages but might also have unwanted adverse ef-fects, such as social isolation and loneliness. We analyze the role of emotional support in understanding loneliness among Chinese international students in Germany, in comparison to local students, from a gender perspective. Based on a representative sample, our findings suggest that Chinese international students feel lonelier than local ones. Female Chinese international students are less lonely compared to male ones, whereas the opposite is true for local students. Contrary to our expectations, a higher number of emotionally supportive ties is associated with higher levels of loneliness for all the students. Our further analysis of the correlation between emotional support and loneliness separately for the four subgroups indicates that while for female local students having more emotionally supportive ties is as-sociated with lower levels of loneliness, for female Chinese international students we find the opposite trend. For all male students, we find no significant effect of emotional support on loneliness. We recommend conducting a longitudinal study for examining the causality of the relationship between networks and loneliness in the future. Results have important implica-tions for universities and higher education research in understanding the role of networks on loneliness.
Keywords: loneliness; personal networks; international student mobility; gender; emotional support

Loneliness among Chinese international and local students in Germany: the role of student status, gender, and emotional support - Bilecen, Başak; Diekmann, Isabell; Faist, Thomas (European Journal of Higher Education)

Kreuzkategorisierungen, kategoriale Verwechslungen und Intersektionalität am Beispiel muslimischer Mädchen*arbeit in der Migrationsgesellschaft - Diekmann, Isabell (Betrifft Mädchen)